Pengaruh Pemberian Probiotik Plus Herbal pada Pakan Komersil terhadap Retensi Protein dan Retensi Lemak Ikan Nila Merah (Oreochromis niloticus) [The Effect of Addition Probiotic Plus Herbal on Commercial Feed to Protein Retention and Fat Retention Red Tilapia Fish (Oreochromis niloticus) ] - Muhammad Arief; Diatra Faradiba; Muhammad Anam Al-Arief (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Red tilapia fish (Oreochromis niloticus) is one of the mainstays of the freshwater fishery which is growing rapidly in Indonesia. The production of red tilapia fish fishery experiences a significant increase from year after year which amounting from 567.078 tons in 2011 to become 695.063 tons in 2012 and 909.016 tons in 2013 ( Directorate General of Aquaculture – Ministry of Marine and Fishery, 2014). The development of red tilapia fish farming were not experiences many issues, but there is one problem that needs to be concern which is about feed problem, the feed that used in aquaculture activities is determine the production costs up to 60-70% of the total production cost incurred (Jusadi et al., 2004). Fish farming business are strongly influenced by the availability of sufficient fodder in numbers and quality to support the growth and life sustainability of fish cultivation. Feed plays an important part for the growth of the fish (Wahyudi, 2010). The feed can increase the quality of fish weight with addition of a feed additive. One of the alternatives that can be take is by adding probiotic (Anggraeni, 2012) and herbal ingredients in feed (Ariyanto et al., 2013). Research results show that the addition of probiotics plus herbs affect the digestibility of protein retention and fat retention red tilapia. Based on the research that has been done, the addition of probiotics plus herbs with a dose of 2 ml / kg of feed can be used as artificial feed supplement and as an alternative to reduce the production cost of cultivation of red tilapia (Oreochromis niloticus).